Building Digital Platform for Property Marketing Sales with an Enterprise Architecture Approach - Djarot Hindarto; Tri Dharma Putra (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Constructing a digital platform is an essential priority in an era where technology is the cornerstone of success in the real estate marketing and sales sector. Nevertheless, the advancement of these platforms is frequently impeded by obstacles pertaining to integration, security, and scalability, which stem from their inadequate establishment. Existing platforms' incapability to rapidly adapt to shifting market dynamics frequently impedes the development of innovative digital solutions for the real estate industry, which provided the impetus for this study. The fundamental objective of this study is to create a framework capable of accommodating scalable business expansion, enhancing data security, and overcoming integration obstacles. Utilizing Enterprise Architecture principles in the design and implementation of the platform, as well as conducting a comprehensive examination of the current IT infrastructure, stakeholder requirements, and mapping of pertinent business processes, will comprise the research methods. The results of this study are expected to contribute to a wholehearted comprehension of how the Enterprise Architecture approach can function as a resilient framework for the development of effective digital platforms. In the contemporary digital age, this platform is expected to furnish solutions capable of swiftly adjusting and reacting to evolving market dynamics and changes, thereby facilitating the marketing and sales requirements of real estate. Finally, this research endeavors to offer a comprehensive and practical perspective on constructing a robust and flexible digital infrastructure that can effectively cater to the demands of the real estate sector in the current era of digitalization.